Remarks at the One Planet Summit on Biodiversity - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about climate change and the loss of biodiversity as defining issues of our time. He insisted on the importance of supporting developing countries in achieving their NDCs, helping them develop long-term strategies for low-carbon and climate-resilient economies, end their reliance on coal, and address biodiversity loss. He highlighted on the announcement of an ambitious target from the World Bank Group for thirty-five percent of financing to have climate co-benefits over the next five years, to help countries rebuild greener and with more resilience, for instance through low-carbon infrastructure and more environmentally-friendly agriculture practices. He mentioned that over the last two years, World Bank Group has supported the creation and consolidation of more than hundred million hectares of Marine and Coastal protected areas along with ten million hectares of terrestrial protected areas in Asia, Africa, and Latin America. Between now and 2025 the World Bank Group will invest more than five billion US dollars to improve livelihoods and restore degradation in the Sahel, Lake Chad, and Horn of Africa regions. This investment, a major contribution to the Great Green Wall, comes at a crucial time, which will help improve livelihoods as countries recover from Coronavirus (COVID-19) while also dealing with the impact of both biodiversity loss and climate change on their people and economies.